The Impact of Livelihood Asset Accumulation on the Well-being and Psychology of Iban Rural Households in Sarawak - Leha, Saliman; Wong, Swee Kiong; Mohd Hairee, Abdullah; Nor Hanim, Awang @ Mohd Noor (Auricle Global Society of Education and Research, 2023)
Despite still engaging in subsistence agriculture, the Iban in Pantu are increasingly embracing commercial and non-agricultural pursuits. The accumulation of various assets is crucial for the livelihood and well-being of the Iban community in Pantu. The assets encompass resources and capabilities that households can leverage to enhance their livelihood strategies. This study investigates the determinants of well-being among rural households in Pantu District Sri Aman, Sarawak, by exploring the accessibility to livelihood assets. The study specifically investigated the correlation between livelihood strategies and the accessibility of human, financial, social, capital, and natural assets. To obtain a comprehensive understanding of the wellbeing and livelihood assets of households and communities, this study used a mixed methods approach that combined structured and in-depth interviews. The qualitative method involved conducting in-depth interviews with two community chiefs (penghulus) and 12 village heads (tuai rumah). A quantitative methodology was utilised in the study, consisting of a structured interview schedule. The collection of data involved the use of disproportionate purposive sampling to reach out to 220 heads of household (bilik family) living in 12 longhouses. The study found that the well-being of the local community is positively affected by the availability of social and natural resources. Available schemes, subsidies, and training provided through vertical and horizontal social integrations have helped the Iban community maintain their livelihood. Notwithstanding the depletion of natural resources in Pantu owing to development, natural capital retains its importance to the community. This study provides insights into asset accumulation strategies and the potential for improving Iban livelihoods in rural Pantu through the discovery of the significance of social and natural assets. Policymakers, development practitioners, and researchers working on sustainable rural development and poverty reduction can gain valuable insights from this study.